2016 IEEE International Parallel and Distributed Processing Symposium (IPDPS) 2016
DOI: 10.1109/ipdps.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

On the Root Causes of Cross-Application I/O Interference in HPC Storage Systems

Abstract: As we move toward the exascale era, performance variability in HPC systems remains a challenge. I/O interference, a major cause of this variability, is becoming more important every day with the growing number of concurrent applications that share larger machines. Earlier research efforts on mitigating I/O interference focus on a single potential cause of interference (e.g., the network). Yet the root causes of I/O interference can be diverse. In this work, we conduct an extensive experimental campaign to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…The capacity of a single HDD-based storage system has reached dozens of PBs (NERSC, 2017b). Although redundant array of independent disks (RAID) has been leveraged to improve the performance of storage systems, HDD's costly overhead of disk-head movements prevents it from meeting the extreme amount of input/output (I/O) and low I/O latency requirements of future exascale systems (Yildiz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of a single HDD-based storage system has reached dozens of PBs (NERSC, 2017b). Although redundant array of independent disks (RAID) has been leveraged to improve the performance of storage systems, HDD's costly overhead of disk-head movements prevents it from meeting the extreme amount of input/output (I/O) and low I/O latency requirements of future exascale systems (Yildiz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Yildiz et al studied the root cause of inter-application I/O interference in HPC storage systems by comparing the impact of different factors [19]. They found that bad flow of control in the I/O path caused interference in most cases.…”
Section: Related Workmentioning
confidence: 99%
“…HDD is known for its significant performance degradation under concurrent workloads. The interference stems from the additional disk‐head movements produced by interleaved requests to distinct file regions . The total bandwidth a storage node can provide is greatly cut down when there is competition.…”
Section: Motivationmentioning
confidence: 99%
“…Many works in this area() have been dedicated to mitigate the increasingly serious problem of cross‐application I/O interference . An I/O orchestration mechanism named TRIO is proposed to coordinate bursty writes of checkpoint data on I/O nodes for better sequential write traffic to storage nodes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation